The Medicago truncatula nodule identity gene MtNOOT1 is required for coordinated apical-basal development of the root - Shen, Defeng (BMC Plant Biol, 2019)
BACKGROUND: Legumes can utilize atmospheric nitrogen by hosting nitrogen-fixing bacteria in special lateral root organs, called nodules. Legume nodules have a unique ontology, despite similarities in the gene networks controlling nodule and lateral root development. It has been shown that Medicago truncatula NODULE ROOT1 (MtNOOT1) is required for the maintenance of nodule identity, preventing the conversion to lateral root development. MtNOOT1 and its orthologs in other plant species -collectively called the NOOT-BOP-COCH-LIKE (NBCL) family- specify boundary formation in various aerial organs. However, MtNOOT1 is not only expressed in nodules and aerial organs, but also in developing roots, where its function remains elusive. RESULTS: We show that Mtnoot1 mutant seedlings display accelerated root elongation due to an enlarged root apical meristem. Also, Mtnoot1 mutant roots are thinner than wild-type and are delayed in xylem cell differentiation. We provide molecular evidence that the affected spatial development of Mtnoot1 mutant roots correlates with delayed induction of genes involved in xylem cell differentiation. This coincides with a basipetal shift of the root zone that is susceptible to rhizobium-secreted symbiotic signal molecules. CONCLUSIONS: Our data show that MtNOOT1 regulates the size of the root apical meristem and vascular differentiation. Our data demonstrate that MtNOOT1 not only functions as a homeotic gene in nodule development but also coordinates the spatial development of the root.